A Descriptive Study of Tooth Brushing Knowledge Among Students at Inpres Kera-Kera Elementary School in Makassar (Journal of Applied Oral Health and Dental Therapy (JAOHDT), 2026)
Background. This study is based on the importance of tooth brushing knowledge as an effort to maintain oral health among elementary school children, considering that proper tooth brushing behavior is still relatively low. Objective. This study aims to describe the level of tooth brushing knowledge among students at Inpres Kera-Kera Elementary School, Makassar City. Methods. This study used a quantitative method with a descriptive approach. The sampling technique used total sampling with 50 respondents from third and fourth grade students. Data were collected using a questionnaire and analyzed using univariate analysis with SPSS. Results. The results showed that the majority of respondents had a good level of knowledge, with 42 respondents (84%), followed by moderate category with 6 respondents (12%), and poor category with 2 respondents (4%). Conclusion. Most students have a good level of knowledge regarding tooth brushing, indicating that dental health education has been fairly effective, although it still needs improvement.
Keywords: knowledge level; tooth brushing; elementary school children